PENGARUH KONSEP DIRI, KOMUNIKASI INTERPERSONAL, DAN EFIKASI DIRI (SELF EFFICACY) TERHADAP KINERJA PUSTAKAWAN DI ERA GLOBALISASI - Gardjito Gardjito (Universitas Negeri Jakarta, 2010)
The objective of this causal research is to obtain information concerning the influence of self concept, interpersonal communication, and self efficacy on librarian performance at the National Library of Indonesia. The research was conducted by using a survey method with path analysis applied in testing hypothesis. In this research, librarian performance has been chosen as a unit analysis and 60 samples of librarian were selected randomly. The results of the research are as follows: (1) There is a direct effect of self concept on librarian performance; (2) There is a direct effect of self concept on self efficacy; (3) There is a direct effect of interpersonal communication on librarian performance; (4) There is a direct effect of interpersonal communication on self efficacy; (5) There is a direct effect of self efficacy on librarian performance; (6) There is an indirect effect of self concept on librarian performance through self efficacy; (7) There is an indirect effect of interpersonal communication on librarian performance through self efficacy. Based on those findings, there are some implications such as research implication, theoretical implication, policy implication and practical implication that could be taken into consideration in developing and empowering librarian performance at the National Library of Indonesia.